The Reaction Specificity of Mammalian ALOX15 Orthologs is Changed During Late Primate Evolution and These Alterations Might Offer Evolutionary Advantages for Hominidae - Heydeck, Dagmar; Reisch, Florian; Schäfer, Marjann; Kakularam, Kumar R.; Roigas, Sophie A.; Stehling, Sabine; Püschel, Gerhard P.; Kuhn, Hartmut (Frontiers in Cell and Developmental Biology, 2022)
Arachidonic acid lipoxygenases (ALOXs) have been implicated in the immune response of mammals. The reaction specificity of these enzymes is decisive for their biological functions and ALOX classification is based on this enzyme property. Comparing the amino acid sequences and the functional properties of selected mammalian ALOX15 orthologs we previously hypothesized that the reaction specificity of these enzymes can be predicted based on their amino acid sequences (Triad Concept) and that mammals, which are ranked in evolution below gibbons, express arachidonic acid 12-lipoxygenating ALOX15 orthologs. In contrast, Hominidae involving the great apes and humans possess 15-lipoxygenating enzymes (Evolutionary Hypothesis). These two hypotheses were based on sequence data of some 60 mammalian ALOX15 orthologs and about half of them were functionally characterized. Here, we compared the ALOX15 sequences of 152 mammals representing all major mammalian subclades expressed 44 novel ALOX15 orthologs and performed extensive mutagenesis studies of their triad determinants. We found that ALOX15 genes are absent in extant Prototheria but that corresponding enzymes frequently occur in Metatheria and Eutheria. More than 90% of them catalyze arachidonic acid 12-lipoxygenation and the Triad Concept is applicable to all of them. Mammals ranked in evolution above gibbons express arachidonic acid 15-lipoxygenating ALOX15 orthologs but enzymes with similar specificity are only present in less than 5% of mammals ranked below gibbons. This data suggests that ALOX15 orthologs have been introduced during Prototheria-Metatheria transition and put the Triad Concept and the Evolutionary Hypothesis on a much broader and more reliable experimental basis.